Circular RNAs: biogenesis, expression and their potential roles in reproduction - Guobo Quan; Julang Li (BMC, 2018)
Abstract Unlike other non-coding RNAs (ncRNAs), circular RNA (circRNA) is generally presented as a covalently linked circle lacking both a 5' cap and a 3' tail. circRNAs were thought to be spliced intermediates, byproducts, or products of abnormal RNA splicing events. However, the high-throughput sequencing technology coupled with bioinformatics has recently uncovered thousands of endogenous circRNAs in cells of many different species. These circRNAs show various features, such as abundant expression, evolutionary conservation, cell- or tissue-specific expression, and a higher resistance to degradation caused by exonuclease or ribonuclease (RNase), suggesting their potentially biological significance. However, the function of these circRNAs, their mechanism of action, and the regulation of their biogenesis and degradation remains largely unclear. The current research and findings of circRNA in the context of reproduction will be reviewed. Additionally, the perspectives of circRNAs in the field will be discussed.